2002
DOI: 10.1128/iai.70.10.5404-5411.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Intracellularly Activated Gene from Salmonella enterica Serovar Typhi

Abstract: A Salmonella enterica serovar Typhi gene that is selectively up-regulated upon bacterial invasion of eukaryotic cells was characterized. The open reading frame encodes a 298-amino-acid hydrophobic polypeptide (30.8 kDa), which is predicted to be an integral membrane protein with nine membrane-spanning domains. The protein is closely related (87 to 94% reliability) to different transport and permease systems. Gene expression under laboratory conditions was relatively weak; however, sevenfold induction was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Necrosis, a passive pattern of cell death, is affected by some physical, chemical and biological factors (Nagarathnamma et al 1997). The results of the present study are in agreement with many other studies conducted on apoptosis where apoptosis has been shown with these DNA binding dyes (Chen et al 1996;Basso et al 2002). Further, detailed characterization and localization of the stress-induced proteins/OMPs will help us to understand better the pathophysiology of the disease under conditions which are more closer to in vivo situations and the mechanisms involved in the pathogenesis.…”
Section: Apoptotic Studiessupporting
confidence: 94%
See 1 more Smart Citation
“…Necrosis, a passive pattern of cell death, is affected by some physical, chemical and biological factors (Nagarathnamma et al 1997). The results of the present study are in agreement with many other studies conducted on apoptosis where apoptosis has been shown with these DNA binding dyes (Chen et al 1996;Basso et al 2002). Further, detailed characterization and localization of the stress-induced proteins/OMPs will help us to understand better the pathophysiology of the disease under conditions which are more closer to in vivo situations and the mechanisms involved in the pathogenesis.…”
Section: Apoptotic Studiessupporting
confidence: 94%
“…Hoechst 33342 and PI (propidium iodide) can bind with DNA, causing a blue or red fluorescence respectively (Basso et al 2002). PI can only permeate through the membrane of dead cells, whereas Hoechst 33342 can permeate through intact membranes as well.…”
Section: Apoptotic Studiesmentioning
confidence: 99%
“…To generate nonpolar mutations of taiA and clyA, the overlap-extension PCR method described by Basso et al (2002) was used. For taiA, fragments were amplified with primers STY1499-BF and STY1499-BR (Table 2) for the 59 end of the gene, and primers STY1499-EF and STY1499-ER for the 39 end of the gene.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of fur, rfrA or rfrB individually or in combination (fur/rfrA, fur/rfrB, fur/ rfrA/rfrB and rfrA/rfrB) was done by allelic exchange as described previously (Faucher et al, 2009) using the overlap-extension PCR method (Basso et al, 2002). Primers are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%